2021
DOI: 10.1038/s41467-021-26343-3
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomic analysis of the tumor ecosystems underlying initiation and progression of papillary thyroid carcinoma

Abstract: The tumor ecosystem of papillary thyroid carcinoma (PTC) is poorly characterized. Using single-cell RNA sequencing, we profile transcriptomes of 158,577 cells from 11 patients’ paratumors, localized/advanced tumors, initially-treated/recurrent lymph nodes and radioactive iodine (RAI)-refractory distant metastases, covering comprehensive clinical courses of PTC. Our data identifies a “cancer-primed” premalignant thyrocyte population with normal morphology but altered transcriptomes. Along the developmental traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 84 publications
8
99
1
Order By: Relevance
“…The aging-associated upregulation of fatty acid metabolism seen in this study may contribute to dysregulation of lipid metabolism in thyroid cancer ( 26 ). A recent single-cell RNA sequencing study confirmed a premalignant state, in which cancer-primed cells with aberrant expression programs have yet to undergo evident changes in cellular morphology ( 27 ). Hence, some caution in interpreting the results is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The aging-associated upregulation of fatty acid metabolism seen in this study may contribute to dysregulation of lipid metabolism in thyroid cancer ( 26 ). A recent single-cell RNA sequencing study confirmed a premalignant state, in which cancer-primed cells with aberrant expression programs have yet to undergo evident changes in cellular morphology ( 27 ). Hence, some caution in interpreting the results is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Single cell RNA sequencing data are extracted from the Gene Expression Omnibus (GEO) database (GSE184362) ( 11 ). The downstream analysis of scRNA-seq (namely, quality control, dimensionality reduction, clustering, differential expression analysis, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…Single-cell transcriptome analyses depicted a more detailed genomic landscape of thyroid cancers, underlying PTC initiation and progression, identifying a premalignant thyrocyte subpopulation that evolves in different malignant states [ 23 ].…”
Section: Signalling Pathways Activated In Thyroid Cancersmentioning
confidence: 99%
“…Mutation hierarchy in thyroid cancers is nicely evidenced by data generated for the most aggressive thyroid cancers, PDTC and ATC, carrying mutations in TERT promoter gene (42.3% in PTDC and 73.5% in ATC), suggesting that the initial BRAF+ve subpopulation is lost during the tumour progression and the TERT+ve cells have a positive growth selection over the others, becoming more aggressive [ 23 ].…”
Section: Signalling Pathways Activated In Thyroid Cancersmentioning
confidence: 99%